2019
DOI: 10.1136/archdischild-2019-318062
|View full text |Cite
|
Sign up to set email alerts
|

Daily life participation in childhood chronic disease: a qualitative study

Abstract: ObjectiveOpportunities to participate in daily life have improved considerably for children with chronic disease. Nevertheless, they still face challenges associated with their ever-present illness affecting every aspect of their lives. To best help these children, we aimed to assess the child’s own perspective on participation and the main considerations that affect participation in a stable phase of disease.MethodsQualitative study design was applied. Semistructured, indepth interviews were conducted and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Our findings reflect those of previous studies, 24 which have also found that young adults with childhood-onset CKD report difficulties with education, employment and social relationships, 25–28 and perceive that their lives are ‘on hold’. 29 30 These problems of life participation have also been documented in studies in young people diagnosed with other childhood chronic conditions, including cystic fibrosis, haematological and autoimmune disease, who also feel impaired in their social interactions and capacity to keep up with peers 31 and have lower life satisfaction. 32 Our study further reveals that young adults believe that missing school and social opportunities, and being ‘overprotected’ during childhood caused them to lack the fundamental skills and confidence for social interaction, and develop independence to participate in life as autonomous adults.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings reflect those of previous studies, 24 which have also found that young adults with childhood-onset CKD report difficulties with education, employment and social relationships, 25–28 and perceive that their lives are ‘on hold’. 29 30 These problems of life participation have also been documented in studies in young people diagnosed with other childhood chronic conditions, including cystic fibrosis, haematological and autoimmune disease, who also feel impaired in their social interactions and capacity to keep up with peers 31 and have lower life satisfaction. 32 Our study further reveals that young adults believe that missing school and social opportunities, and being ‘overprotected’ during childhood caused them to lack the fundamental skills and confidence for social interaction, and develop independence to participate in life as autonomous adults.…”
Section: Discussionmentioning
confidence: 93%
“…1 We previously described the child's perspective on 'full participation' among children with a chronic disease. 6 We found that these children feel that participation encompasses more than engaging in activities; indeed, they described having a sense of belonging, the ability to affect social interactions, and the capacity to keep up with healthy peers as key elements. [6][7][8][9][10] Parents form their child's primary social network and can have a major impact on their child's daily life participation, especially because the presence of a chronic disease can affect the parent-child relationship and What is known about the subject?…”
Section: Introductionmentioning
confidence: 77%
“… 1 We previously described the child’s perspective on ‘full participation’ among children with a chronic disease. 6 We found that these children feel that participation encompasses more than engaging in activities; indeed, they described having a sense of belonging, the ability to affect social interactions, and the capacity to keep up with healthy peers as key elements. 6–10 …”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations